Optimizing Administration of Registration and Issuance of Replacement Certificates: Optimasi Administrasi Pendaftaran dan Penerbitan Sertifikat Pengganti - Mohammad Fadhil Wibowo; M. Kasim M; Arbainah Saidi; Rusli Rusli (Academia Open, 2025)
General Background: The administration of registration, issuance, and delivery of replacement land certificates is a crucial component of land services in Indonesia to ensure legal certainty of land ownership; however, its implementation often faces administrative and technical challenges. Specific Background: At the Samarinda City Land Office, this process includes the registration of the Land Registration Certificate, field inspections, public announcements in mass media, and final certificate delivery, which are largely conducted in accordance with regulations but still encounter obstacles. Knowledge Gap: Empirical studies examining the supporting and inhibiting factors of replacement certificate administration at the city level remain limited. Aims: This study aims to analyze the implementation of replacement certificate administration at the Samarinda City Land Office and identify factors that support and hinder the process. Results: Using a qualitative approach through interviews, observations, and documentation, the study found that integration of the KKP database and adequate human resources were the main supporting factors, while constraints included incomplete applicant documents, lack of survey copies, and ineffective communication between officers and applicants. Novelty: This research provides a detailed empirical overview of the dynamics of replacement certificate administration at the municipal level and emphasizes the importance of active applicant involvement. Implications: Recommendations include enhancing public outreach, strengthening staff capacity, and optimizing land information systems to improve the effectiveness of public services. Highlights: Highlights integration of KKP database as a key enabler. Identifies main obstacles in document completeness and communication. Emphasizes active applicant involvement in speeding up processes. Keywords: Replacement Certificate, Land Administration, Public Service, Legal Certainty